Integrating MRI brain imaging studies of pre-reading children with current theories of developmental dyslexia: a review and quantitative meta-analysis. (August 2016) - Vandermosten, Maaike; Hoeft, Fumiko; Norton, Elizabeth S
Highlights: The core neurobiological cause of dyslexia is still not fully understood. Brain anomalies in adults with dyslexia might be either a consequence or cause. This qualitative and quantitative review focuses on MRI studies in pre-readers. At-risk pre-readers display reliable left temporo-parietal and occipito-temporal differences. Early connectivity problems fit with a multifactorial theory of dyslexia. Abstract : The neurobiological substrates that cause people with dyslexia to experience difficulty in acquiring accurate and fluent reading skills are still largely unknown. Although structural and functional brain anomalies associated with dyslexia have been reported in adults and school-age children, these anomalies may represent differences in reading experience rather than the etiology of dyslexia. Conducting MRI studies of pre-readers at risk for dyslexia is one approach that enables us to identify brain alterations that exist before differences in reading experience emerge. The current review summarizes MRI studies that examine brain differences associated with risk for dyslexia in children before reading instruction and meta-analyzes these studies. In order to link these findings with current etiological theories of dyslexia, we focus on studies that take a modular perspective rather than a network approach. Although some of the observed differences in pre-readers at risk for dyslexia may still be shaped by language experiences during the first years of life, such studies underscore the existence of reading-related brain anomalies prior to reading onset and could eventually lead to earlier and more precise diagnosis and treatment of dyslexia.